New applications of the functional variable method - İnç, Mustafa; Inan, Ibrahim E.; Ugurlu, Yavuz (Elsevier Gmbh, Urban & Fischer Verlag, 2017)
In this paper, we study the different types of soliton solutions of the Zoomeron equation and Hirota-Satsuma coupled KdV (HSCKdV) system with the aid of the functional variable method (FVM). Then, we get some special solutions like the bell shaped, triangular and kink soliton solutions. We present the parametric restriction on the coefficients for the existence of obtained solitons. Finally, the remarkable features of such solitons are demonstrated in some figures. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Functional variable method; Zoomeron equation; HSCKdV system